2008
DOI: 10.1103/physrevb.77.184302
|View full text |Cite
|
Sign up to set email alerts
|

Complex superlattice unit cell designs for reduced thermal conductivity

Abstract: The suitability of the Green-Kubo method for predicting the thermal conductivity of nanocomposites is assessed by studying model Lennard-Jones superlattices. Good agreement is found when comparing the predicted cross-plane thermal conductivities to independent predictions from the direct method. The link between the superlattice unit cell design and the thermal conductivity tensor is then explored. We find that complex, multilayered unit cell designs can reduce the cross-plane thermal conductivity by 17% compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
133
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(144 citation statements)
references
References 55 publications
10
133
1
Order By: Relevance
“…[19] in the study of superlattice structures. They found that the oscillation in their work is caused by specific zero-wave-vector optical phonon modes and can be removed when a different definition of the heat current based on the equilibrium atom positions is used [19].…”
Section: Core/shell Nanowire Structure and The Coherent Resonancementioning
confidence: 99%
“…[19] in the study of superlattice structures. They found that the oscillation in their work is caused by specific zero-wave-vector optical phonon modes and can be removed when a different definition of the heat current based on the equilibrium atom positions is used [19].…”
Section: Core/shell Nanowire Structure and The Coherent Resonancementioning
confidence: 99%
“…While both indicate NPM thermal conductivity reduction, the EMD predictions are higher than their counterparts from the NEMD simulations. This discrepancy between the two sets of predictions is not uncommon because the EMD and NEMD methods depend on different factors for their accuracy [20,31].…”
mentioning
confidence: 99%
“…(3) definition of q z exhibits fast oscillations that are associated with high-frequency optical modes. Landry et al 28 pointed out that these fast oscillations are related to the first sum in Eq. (3).…”
Section: B Nemd Determination Of Kmentioning
confidence: 99%